The power of oratory in the medieval Muslim world - Jones, Linda Gale (Cambridge studies in Islamic civilization, 2012)
A remarkable book analyzing the importance of oratory for transmitting religious knowledge, legitimizing rulers, and inculcating moral values in the medieval Islamic world.